BUSINESS MODEL INNOVATION OF HOTELS IN VIETNAM DURING THE COVID-19 PANDEMIC - Nguyen, Thuy Anh; Tran, Thi Phuong Uyen; Nguyen, Thi Hong Ngoc; Nguyen, Bao Ngoc; Pham, Khoa Loc; Khong, Le Chi Thanh (Graduate Program of Universitas Tarumanagara, 2023)
The tourism sector encountered significant difficulties in sustaining operations amidst the global economic downturn caused by the COVID-19 pandemic. Initial observations within the hospitality industry suggest that redesigning the business models could be a key solution for recovery. However, there is a scarcity of empirical studies on this topic, particularly in the hotel industry. To address both practical and theoretical gaps, the authors conducted a study on business model innovation of hotels in Hanoi during the COVID-19 pandemic. The study involved 300 participants with diverse genders and roles working in high ranking lodging units, aiming to evaluate how hotel firms transformed their business models from the perspective of industry professionals. The results indicated that factors such as the business environment, the impact of the COVID-19 pandemic, and a culture of innovation positively influenced the degree of business model innovation among hotel firms. Furthermore, a higher level of business model innovation was found to have positive effects not only in the short term but also on overall business performance.